Reliability On Yield Contributing Characters For Improving Yield Potential In Paprika (Capsicum Annuum L.) (Applied Biological Research, 2019)
Forty four genotypes of paprika (Capsicum annuum L.) were evaluated at  Horticultural Research Station, Lam farm, Guntur (India) in the year 2017 to  assess variability, character association and path analysis among the yield and  yield attributing characters. High magnitudeof PCV and GCV were observed  for characters viz., number of fruits plant-1, fruit diameter and dry fruit yield  plant-1. Predominance of additive gene action was observed for days to  maturity, number of fruits plant-1, fruit length, fruit diameter, number of  seeds fruit-1 and dry fruit yield plant-1 which may be exploited through simple selection. Dry fruit yield plant-1 showed positive significant correlation with the number of fruits plant-1. The path analysis revealed that the number of  fruits plant-1, fruit length and fruit diameter had positive direct effect on yield  plant-1 indicating that direct selection based on these traits may be helpful in  evolving high yielding varieties of paprika.
Keywords: Capsicum annuum; genetic advance; genetic variability; heritability; paprika; path analysis